Final Astro-2 calibration of the Hopkins Ultraviolet Telescope - ESPEY, BRIAN RUSSELL (University of Chicago Press, 1999)
We present the ?nal calibration of the Hopkins Ultraviolet Telescope (HUT) for its ?ight during the Astro-2 space shuttle mission in 1995 March. Aspects of mission operations and instrument performance that a?ect data quality are described in detail, as are the data reduction procedures applied to the archived data. The sensitivity calibration is de?ned by a comparison between synthetic spectra and observations obtained in ?ight of the hot DA white dwarfs HZ 43, GD 71, GD 153, and G191-B2B; the synthetic spectra were calculated by D. Koester using model parameters derived from ?ts to groundbased spectra. The resulting ?ux-calibrated spectra for these stars di?er from their respective model predictions by less than 3% at all wavelengths, except at the cores of the Lyman lines where the observed line pro?les are shallower than the predicted pro?les. As an additional consistency check, the HUT spectrum of BD ]75!325 was found to di?er from the Hubble Space Telescope Faint Object Spectrograph spectrum by at most 5% in the region of overlap. The wavelength scale and spectral resolution were calibrated by observations of symbiotic stars and of the coronal star a Aur. The spectral resolution was found to vary from 1.8 to roughly 4.5 A? , depending on wavelength and on the instrument con?guration. The internal consistency of the HUT calibration provides a new and important test of white dwarf model atmospheres, as the predicted stellar spectra are more sensitive to changes in model parameters or to shortcomings in the models themselves at wavelengths shortward of 1100 A? than at longer wavelengths. Combining this result with that of the Astro-1 HUT calibration (that a synthetic spectrum of G191-B2B and laboratory ?ux standards gave results consistent within the laboratory measurement uncertainties) demonstrates that pure hydrogen white dwarfs with e?ective temperatures of 32,000E61,000 K may be used as primary ?ux standards down to the Galactic Lyman edge.
PUBLISHED
Keywords: Physics